Hypofractionated Radiotherapy and Stereotactic Boost with Concurrent and Adjuvant Temozolamide for Glioblastoma in Good Performance Status Elderly Patients – Early Results of a Phase II Trial - Floyd, Scott; Wong, Eric; Uhlmann, Eric; Fonkem, Ekokobe; Kasper, Ekkehard; Mahadevan, Anand (Frontiers in Oncology, 2012)
Glioblastoma Multiforme (GBM) is an aggressive primary brain neoplasm with dismal prognosis. Based on successful phase III trials, 60 Gy involved-field radiotherapy in 30 fractions over 6 weeks [Standard radiation therapy (RT)] with concurrent and adjuvant temozolomide is currently the standard of care. In this disease, age and Karnofsky Performance Status (KPS) are the most important prognostic factors. For elderly patients, clinical trials comparing standard RT with radiotherapy abbreviated to 40 Gy in 15 fractions over 3 weeks demonstrated similar outcomes, indicating shortened radiotherapy may be an appropriate option for elderly patients. However, these trials did not include temozolomide chemotherapy, and included patients with poor KPS, possibly obscuring benefits of more aggressive treatment for some elderly patients. We conducted a prospective Phase II trial to examine the efficacy of a hypofractionated radiation course followed by a stereotactic boost with concurrent and adjuvant temozolomide chemotherapy in elderly patients with good performance status. In this study, patients 65 years and older with a KPS > 70 and histologically confirmed GBM received 40 Gy in 15 fractions with 3D conformal technique followed by a 1–3 fraction stereotactic boost to the enhancing tumor. All patients also received concurrent and adjuvant temozolomide. Patients were evaluated 1 month post-treatment and every 2 months thereafter. Between 2007 and 2010, 20 patients (9 males and 11 females) were enrolled in this study. The median age was 75.4 years (range 65–87 years). At a median follow-up of 11 months (range 7–32 months), 12 patients progressed and 5 are alive. The median progression free survival was 11 months and the median overall survival was 13 months. There was no additional toxicity. These results indicate that elderly patients with good KPS can achieve outcomes comparable to the current standard of care using an abbreviated radiotherapy course, radiosurgery boost, and temozolomide.